The Application of Realistic Mathematics Education Learning Models in Fraction Numbers Material to Improve Learning Outcomes of Middle School Students - Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2018)
Learning outcomes are one of the benchmarks of successful learning activities. This study aims to determine the improvement of student learning outcomes in studying Fractional Numbers with the application of Realistic Mathematic Education (RME) learning model. The type of research used is Classroom Action Research (PTK). The study was designed using 2 cycles in each cycle consisting of 4 stages: planning, action, observation, and reflection. Based on result of analysis, student activity at cycle 1 73.54% and cycle II equal to 86,35%. While the learning outcomes obtained average score 67 on cycle 1 and cycle 2 reached score 84. It proves that the activities and student learning outcomes can be increased by applying the learning model RME. For certain subjects, the RME learning model is used to avoid saturation in learning activities. Keywords: Realistics Mathematic Education (RME), Learning Outcomes